Individualising the dose of allopurinol in patients with gout. (28th May 2017) - Kannangara, Diluk R. W.; Graham, Garry G.; Wright, Daniel F. B.; Stocker, Sophie L.; Portek, Ian; Pile, Kevin D.; Barclay, Murray L.; Williams, Kenneth M.; Stamp, Lisa K.; Day, Richard O.
Abstract : Aims: The aims of the study were to: 1) determine if a plasma oxypurinol concentration –response relationship or an allopurinol dose –response relationship best predicts the dose requirements of allopurinol in the treatment of gout; and 2) to construct a nomogram for calculating the optimum maintenance dose of allopurinol to achieve target serum urate (SU) concentrations. Methods: A nonlinear regression analysis was used to examine the plasma oxypurinol concentration– and allopurinol dose –response relationships with serum urate. In 81 patients (205 samples), creatinine clearance (CLCR ), concomitant diuretic use and SU concentrations before (UP ) and during (UT ) treatment were monitored across a range of allopurinol doses (D, 50–700 mg daily). Plasma concentrations of oxypurinol (C) were measured in 47 patients (98 samples). Models ( n  = 47 patients) and predictions from each relationship were compared using F ‐tests, r 2 values and paired t ‐tests. The best model was used to construct a nomogram. Results: The final plasma oxypurinol concentration –response relationship ( U T  =  U P  –  C *( U P  –  U R )/( ID 50  +  C ), r 2  = 0.64) and allopurinol dose –response relationship (UT  = UP  – D * (UP  – UR )/(ID50  + D), r 2  = 0.60) did not include CLCR or diuretic use as covariates. There was no difference ( P  = 0.87) between the predicted SU concentrations derived from the oxypurinol concentration– and allopurinol dose –response relationships. The nomogram constructed using the allopurinol dose –response relationship for all recruited patients ( n  = 81 patients) required pretreatment SU as the predictor of allopurinol maintenance dose. Conclusions: Plasma oxypurinol concentrations, CLCR and diuretic status are not required to predict the maintenance dose of allopurinol. Using the nomogram, the maintenance dose of allopurinol estimated to reach target concentrations can be predicted from UP .